KARAKTERISTIK MORFOLOGI TEGAKAN AREN GENJAH (Arenga pinnata ( Wurmb) Merr.) DI DESA TAMEMONGGA, KECAMATAN TOMMO, KABUPATEN MAMUJU, SULAWESI BARAT. - GUNAWAN M GUNAWAN; Muliana Djafar; Nirawati Nirawati (Jurnal Eboni, 2021)
ABSTRACT Gunawan M, Morphological Characteristics of Early Aren (Arenga pinnata (Wurmb) Merr.) stands in Tamemongga Village, Tommo District, Mamuju Regency, West Sulawesi, supervised by Muliana Djafar and Nirawati. This research was conducted in Tamemongga Village, Tommo District, Mamuju Regency, Sulawesi. This location was chosen with the consideration that there is still a lack of research on the morphological characteristics of early maturing sugar palm stands. The observation method used is the observation method with the location selected by purposive sampling. Observations were made on the sugar palm population in Tamemongga Village, Tommo District, Mamuju Regency, West Sulawesi. Parameters observed were morphological characters which included vegetative and generative characters. The results showed that almost all vegetative characters had various coefficients of diversity, and generative morphological characteristics for all parameters had low diversity. Keywords: Palm sugar early, vegetative, Generative Diversity.